A Day & an Eternity - Hepp, Anna (Germany, 2009)
The director follows the last days of her 94-year old grandmother, living alone, accompanied by the camera in the confines of her apartment. A black-and-white elegy of a long life, a document of an impending farewell to a loved one.
Verzio Film Festival Submission
Keywords: Documentary films